Media coverage of Malaysian Airline Flight MH370: a preliminary study on the framing of the crisis in the Malaysian mainstream and alternative newspapers - Lim, Shiang Shiang; Ihediwa Samuel Chibundu,; Sharon Jacqueline A/P Albert Wilson, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study proposes to investigate and compare the coverage of the disappearance of Malaysia Airlines flight MH370 by Malaysian mainstream and alternative newspapers – The Star newspaper and Malaysiakini. The MH370 crisis in March 2014 is considered as the greatest aviation crisis in the history of Malaysia because of its magnitude and attracted massive local and international media coverage. It presented Malaysian authorities with a new form of challenge, resulting in various criticisms from aviation, media and crisis communication experts over how information regarding the crisis was handled by Malaysia Airlines (MAS) in particular, and the Malaysian government in general. On the other hand, the role of the media during a crisis is not only to provide information regarding the crisis, but also to act as the peoples' advocate by providing an avenue for public engagements and discussions. However, the ability of the media to play this role depends to a certain extent on ownership, and a large extent on the degree of freedom it enjoys in a country. Through quantitative content analysis, the study compares the framing of the crisis by the selected newspapers, the sources of information for their news stories, and slants of the news. The study found that the mainstream newspaper The Star provided general and limited viewpoints with a concentration on the human interest frame, while the alternative newspaper, Malaysiakini, had more critical news reports with a focus on the attribute of responsibility frame.